Effect of Na2CO3/Al2O3 ratio on the calcium fluoroaluminosilicate-based bioactive glass-ceramics derived from waste materials - Ismail, Nur Quratul Aini; Sa'at, Nor Kamilah; Mohd Zaid, Mohd Hafiz; Zainuddin, Norhazlin; Mayzan, Mohd Zul Hilmi (Elsevier, 2024)
The development and fabrication of bioactive glass (bioglass)-ceramics derived from waste materials enhance the mechanical properties of calcium fluoroaluminosilicate based bioglass-ceramics for biomedical applications. This study aims to examine the effect of the Na2CO3/Al2O3 ratio on the 44SLS-(20-x) Na2CO3-24ES-6P2O5-6CaF2-xAl2O3 system where x = (0,3,6, and 9 wt) as well as its mechanical performance. Structural and microstructural properties were analysed using X-ray diffraction (XRD) and scanning electron microscopy (SEM). In the interim, the density of glass ceramic samples was measured using the method of Archimedes. Afterwards, the bioglass ceramics with the Na2CO3/Al2O3 ratio of 11/9 sintered at 950 °C exhibited excellent results in terms of density that is 2.734 g/cm3. XRD analysis also confirmed the increase in crystallisation of anorthite, fluorapatite and nacaphite. Moreover, SEM analysis revealed the morphology of round-shaped fluorapatite with a variation in the size of sintered glass ceramics. The optimal compressive strength of 136.58 MPa is in the range of human cortical bone. © 2023